EVALUATION SYSTEM FOR LEAN KNOWLEDGE MANAGEMENT ABILITY BASED ON IMPROVED GRAY CORRELATION ANALYSIS - Zhang, Bo; Niu, Zhanwen; Feng, Lijie; Wang, Xiaoqiu (International Journal of Industrial Engineering: Theory, Applications and Practice, 2021)
The efficient implementation of lean production requires an accurate understanding of effective lean knowledge management. However, the existing literature lacks research on evaluating lean knowledge management abilities. To accurately measure lean knowledge management levels, this study established an evaluation index system, selected an improved gray correlation analysis method to determine index weights at all levels, and built a comprehensive evaluation model based on lean knowledge acquisition, integration, and application. Descriptive statistics were calculated from a questionnaire on the current situation of knowledge management in a lean implementation process. By comprehensively evaluating the lean knowledge management abilities of the 28 surveyed enterprises, it was determined that knowledge management can promote improvements therein. The research results provide a decision-making basis for enterprises to formulate a lean implementation strategy.